2019
DOI: 10.1259/bjr.20190150
|View full text |Cite
|
Sign up to set email alerts
|

Deep inspiration breath-hold intensity modulated radiation therapy in a large clinical series of 239 left-sided breast cancer patients: a dosimetric analysis of organs at risk doses and clinical feasibility from a single center experience

Abstract: Objective: To evaluate dose to organs at risk, target coverage and treatment compliance in left-sided breast cancer patients (LSBCP) treated with deep inspiration breath-hold (DIBH) and intensity modulated radiation therapy (IMRT) technique in a contest of daily clinical practice. Methods: A total of 280 consecutive LSBCP referred for adjuvant radiotherapy were systematically screened for suitability of DIBH technique. 239 were able to comply with the requirement for DIBH. Whole breast or chest wall were irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Besides heart radiation exposure, lungs dose represents another relevant endpoint when considering acute and late toxicities (like radiation pneumonitis and brosis) during and after breast cancer irradiation. In agreement with previous studies [24][25][26], we also showed that the mDIBH technique signi cantly reduced left lung dose. This might seem counterintuitive at rst, since more lung volume is within the tangential beam when the heart moves out of the treatment eld during mDIBH, but through in ation, only low density lung tissue remains within the tangential eld, thus avoiding its deterioration.…”
Section: Discussionsupporting
confidence: 93%
“…Besides heart radiation exposure, lungs dose represents another relevant endpoint when considering acute and late toxicities (like radiation pneumonitis and brosis) during and after breast cancer irradiation. In agreement with previous studies [24][25][26], we also showed that the mDIBH technique signi cantly reduced left lung dose. This might seem counterintuitive at rst, since more lung volume is within the tangential beam when the heart moves out of the treatment eld during mDIBH, but through in ation, only low density lung tissue remains within the tangential eld, thus avoiding its deterioration.…”
Section: Discussionsupporting
confidence: 93%
“…To ensure the accuracy of radiation therapy and reduce the patient’s additional radiation dose, optical surface imaging (OSI) systems [ 17 , 18 ] play an increasingly important role in breast radiation therapy. Furthermore, to reduce the radiation dose to the lung and the heart, changing the patient’s position [ 13 , 19 , 20 ] and using deep inspiration breath-hold (DIBH) [ 21 , 22 ] technology were studied. Based on these studies, we will combine OSI and DIBH technology with the new vacuum bag in a further study.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of the DIBH technique in reducing the radiation dose to the LAD have recently been reported [10][11][12][13]; however, delineation of the LAD requires an injection of a contrast agent, which is not usually performed in our clinical practice. We contoured the anterior interventricular groove from its origin down to the apex of the heart as the LAD region.…”
Section: Introductionmentioning
confidence: 99%